Management and the arts - Byrnes, William J. (Elsevier Focal Press, 2009)
Management and the Arts, Fourth Edition provides you with theory and practical applications from all management perspectives including planning, marketing, finance, economics, organizational, staffing, and group dynamics ALL related to an arts organization. Whether you are a manager in a theatre, museum, dance company, or opera, you will gain useful insights into management. Topics written especially to help you with your management skills include: * How arts organizations and management evolved * The theories and processes behind strategic planning and decision making * Organizing and organiz.